Malignant peripheral nerve sheath tumours: an outcome analysis of 32 patients in Lerdsin Hospital, Thailand - Goh, Kian Liang; Kiatisevi, Piya; Sukanthanak, Bhasanan; Piakong, Pongsiri (2018)
Objectives Malignant peripheral nerve sheath tumours (MPNST) are rare soft tissue sarcoma which exhibit a biologically aggressive behaviour with propensity for rapid progression and high mortality rate. Our objectives were to identify the prognostic factors for local recurrence and distant metastasis, to analyse the survival outcome and to identify the prognostic factors related to patients’ survival.